Web developer's cookbook more than 300 ready-made PHP, JavaScript, and CSS recipes - Nixon, Robin 1961- (New York McGraw-Hill, 2012)
"300+ ready-to-use solutions for PHP, JavaScript, and CSSWeb Developers Cookbook offers a comprehensive suite of ready-to-use solutions for PHP, JavaScript, and CSS--among the most commonly used and most versatile open-source languages in the Web developer's toolkit. This hands-on guide assumes a basic acquaintance with Web development techniques. All examples in the book are extensively documented and explained so that even novice developers will be able to understand, use, and learn from them. This practical resource contains more than 300 recipe-like examples, each with accompanying screenshots, tables of the variables and functions used, and extensive explanations of how they work.Web Developers Cookbook Includes more than 300 ready-to-use, cross-referenced recipes that provide instant, dynamic solutions for Web developers--styles, text effects, forms and validation, security, animation, audio and visual effects, and much more Contains examples that are fully tested and up to date with the latest features Explains every part of each recipe in detail, accompanied by graphics, figures, tables and program listings Enables you to quickly add ready-made code snippets to your projects, saving hours of development and debugging time Provides the ultimate time-saver for Web developers Coverage includes: PHP Recipes:Text Processing; Image Handling; Content Management; Forms and User Input; The Internet; Chat, Messaging and Bulletin Boards; MySQL, Authentication and Cookies; Integrating with Third Party Services; Incorporating JavaScript; Diverse Solutions JavaScript Recipes: Core Plug-ins; Location and Dimensions; Visibility; Movement and Animation; Chaining and Interaction; Menus and Navigation; Text Effects; Audio and Visual Effects; Cookies, Ajax and Security; Forms and Validation; Solutions to Common Problems CSS Recipes: Manipulating Objects; Text and Typography; Menus and Navigation; Page Layout; Visual Effects; Objects; Text and Typography; Interaction; Incorporating JavaScript; Superclasses "--
Machine generated contents note: Part I: Getting Started -- Ch 1. Introduction to the three technologies -- Ch 2. Preparing a suitable development environment -- Part II: PHP Recipes -- Ch 3. Text Processing -- Ch 4. Image Handling -- Ch 5. Content Management -- Ch 6. Forms and User Input -- Ch 7. The Internet -- Ch 8. Chat, Messaging and Bulletin Boards -- Ch 9. MySQL, Authentication and Cookies -- Ch 10. Integrating with Third Party Services -- Ch 11. Incorporating JavaScript -- Ch 12. Diverse Solutions -- Part III: JavaScript Recipes -- Ch 13. Core Plug-ins -- Ch 14. Location and Dimensions -- Ch 15. Visibility -- Ch 16. Movement and Animation -- Ch 17. Chaining and Interaction -- Ch 18. Menus and Navigation -- Ch 19. Text Effects -- Ch 20. Audio and Visual Effects -- Ch 21. Cookies, Ajax and Security -- Ch 22. Forms and Validation -- Ch 23. Solutions to common problems -- Part IV: CSS Recipes -- Ch 24. Manipulating Objects -- Ch 25. Text and Typography -- Ch 26. Menus and Navigation -- Ch 27. Page Layout -- Ch 28. Visual Effects -- Ch 29. Objects -- Ch 30. Text and Typography -- Ch 31. Interaction -- Ch 32. Incorporating JavaScript -- Ch 33. Superclasses
Includes index
1
Keywords: COMPUTERS / Web / Web Programming; Cascading style sheets; JavaScript (Computer program language); PHP (Computer program language); Web site development